2020
DOI: 10.1108/pr-12-2018-0527
|View full text |Cite
|
Sign up to set email alerts
|

The effects of responsible leadership and knowledge sharing on job performance among knowledge workers

Abstract: PurposeDrawing upon social exchange theory, this study justified the indirect effects of responsible leadership and knowledge sharing on job performance through the mediation of work engagement and helping initiatives. Job tenure was examined as a moderator.Design/methodology/approachThe hypotheses of this study were empirically tested with structural equation modeling (SEM) and moderated regression analyses. This study conducted a field survey on 512 knowledge workers who employed a high portion of or highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 59 publications
2
71
0
1
Order By: Relevance
“…In Asian context, specific research investigates RL's effect on micro, meso and macro-level outcomes like unethical pro-organizational behaviour, talent retention, organizational citizenship behaviour, environmental performance, job performance and pandemic management (Yasin et al, 2020;Javed et al, 2020a;Afsar et al, 2020;Zhao and Zhou, 2019;Haque et al, 2019aHaque et al, , 2019bHan et al, 2019;Mehta et al, 2020;Lin et al, 2020). While exploring the Western developed notion of RL in the Asian context, Koh et al (2018) observed that Asian leaders possessed values and traits accordant with the Western concept of RL.…”
Section: Peeking Through the Asian Context Of Pakistanmentioning
confidence: 99%
“…In Asian context, specific research investigates RL's effect on micro, meso and macro-level outcomes like unethical pro-organizational behaviour, talent retention, organizational citizenship behaviour, environmental performance, job performance and pandemic management (Yasin et al, 2020;Javed et al, 2020a;Afsar et al, 2020;Zhao and Zhou, 2019;Haque et al, 2019aHaque et al, , 2019bHan et al, 2019;Mehta et al, 2020;Lin et al, 2020). While exploring the Western developed notion of RL in the Asian context, Koh et al (2018) observed that Asian leaders possessed values and traits accordant with the Western concept of RL.…”
Section: Peeking Through the Asian Context Of Pakistanmentioning
confidence: 99%
“…Several studies applied social psychological frameworks such as social exchange theory [70], social identity theory (SIT) [91,99,100], social identity theory of leadership (SITL) [64] and social cognitive theory [81], which all put an emphasis on social mechanisms…”
Section: Theoretical Framework In Selected Studiesmentioning
confidence: 99%
“…Several studies applied social psychological frameworks such as social exchange theory [70], social identity theory (SIT) [91,99,100], social identity theory of leadership (SITL) [64] and social cognitive theory [81], which all put an emphasis on social mechanisms between individuals or between members in groups. Role theory was applied in a few of the studies [67,79], much in line with the conceptualization of the roles model of responsible leadership [18], where the responsible leader has different roles to play according to different contexts.…”
Section: Theoretical Framework In Selected Studiesmentioning
confidence: 99%
“…Success of knowledge management is closely related to staff’s collective sharing of knowledge, skills and experience, which has been increasingly recognized as a significant relevant in promoting creativity, problem solving, and decision making of individuals, teams and even organizations (Bhatti et al, 2020; Song et al, 2017; Yang & Song, 2016; Yuan et al, 2018; Zhang et al, 2016). What’s more, peer knowledge sharing has been proven to have positive impact on organizational performance (i.e., innovation performance, financial performance, individual job performance) (Lin et al, 2020; Muhammed & Zaim, 2020). Despite the various benefits of knowledge sharing, some employees are frequently reluctant to share their knowledge, because it sometimes turns their valuable information into a public good.…”
Section: Introductionmentioning
confidence: 99%